Evaluation of Hydatid Cyst Cases: A Single-center Retrospective Study - Suzan Şahin; Bülent Kaya (Türkiye Parazitoloji Dergisi)
Objective: Cystic echinococcosis (CE) is a zoonotic condition that can be encountered, particularly in developing countries, and leads to significant economic losses. This study was planned to observe the treatment options, complications, in the patients we followed. Methods: Patients aged 18 and over who were diagnosed with hydatid cyst and followed in our hospital between January 2018 and December 2023 were included in the study. Data were obtained from the hospital’s record system. The patients with CE were retrospectively evaluated in terms of age, gender, cyst location, treatment method applied, presence of relapse, and complications. Results: A total of 30 patients, with a mean age of 42.8 years (range: 19-68), were included in the study; 13 (43.3%) were male and 17 (56.7%) were female. The most common presenting complaint was abdominal pain (n=14, 46.7%), and 6 patients (20.0%) were asymptomatic. Sixteen patients had multiple cysts in the same region, and 6 patients had cysts in different regions. The most common site of involvement was the liver (n=21, 70.0%), followed by the lungs in 4 patients (13.3%). Single cases of brain, spinal cord, spleen, kidney, and bone involvement were observed. Diagnosis was made by ultrasonography in 16 patients (53.3%), magnetic resonance imaging in 8 patients (26.7%), and computed tomography in 6 patients (20.0%). Surgical intervention was performed in 20 patients (66.7%), and percutaneous drainage in 3 patients (10.0%). All patients received albendazole treatment. Complications included intra-abdominal abscess in three patients (10.0%) and rupture in one patient. One patient with intracranial involvement died. Conclusion: Although observed worldwide, CE maintain their importance in terms of morbidity and mortality, particularly in developing countries.